CONTEXTUALIZING ISLAMIC LAW IN THE ERA OF DISRUPTION: THE STRATEGIC ROLE OF NAHDLATUL ULAMA IN NAVIGATING RELIGIOUS, POLITICAL, AND EDUCATIONAL CHALLENGES - Syarifah , Masykurotus; Jamal, Nur; Karim, Muhammad Mujib (IQTISODINA, 2025)
The era of disruption has triggered profound shifts in various dimensions of human life, notably in the spheres of religion, politics, and education. These transformations necessitate a dynamic reinterpretation and application of Islamic law to ensure its continued relevance and efficacy. Nahdlatul Ulama (NU), the largest Islamic organization in Indonesia, plays a pivotal role in contextualizing Islamic legal thought to respond to contemporary social dynamics. This study explores NU’s adaptive legal approaches in addressing the challenges posed by digital disruption and socio-political changes. These efforts have proven instrumental in addressing current issues related to religious life, cultural politics, and educational reform in an increasingly disrupted world.